Analysis of self‐oscillating switched‐mode circuit for low‐voltage energy harvesting. Issue 15 (1st July 2013) - Chini, A.
Abstract : The operation of a self‐oscillating switched‐mode circuit topology for low‐voltage thermal energy harvesting is analysed and experimental efficiency results are presented. Circuit self‐start‐up function as well as high‐efficiency power transfer are obtained by using only one transformer without additional inductors. It is shown that even without using a maximum power point tracking (MPPT) tracking circuit, it is possible to achieve efficiencies up to 65% over a relatively broad input voltage range which can be optimised by properly varying the transformer turns ratio n .